Contemporary Balkan cinema : transnational exchanges and global circuits - Papadimitriou, Lydia, 1966-; Grgić, Ana (Traditions in world cinema., 2020)
This edited collection examines post-2008 developments in Balkan cinema in terms of aesthetics and industry. It provides critical and comprehensive profiles of the cinematic output in each Balkan country, while stressing transnational links, global networks and cross-cultural exchanges.